Characterization of interactions between cromolyn sodium and bovine serum albumin by spectroscopic, calorimetric and computational methods. Issue 3 (11th February 2020) - Yasmeen, Shama; Riyazuddeen,; Khatun, Samima; Abul Qais, Faizan
Abstract: Cromolyn sodium (CS), an anti-inflammatory drug is used in the treatment of allergic disorders. Bovine serum albumin (BSA) a blood plasma protein is used as a model protein for studying protein folding and ligand binding mechanism as it is the main transporter protein which decides the disposition and pharmacodynamics of numerous drugs. In this study, interaction of CS with BSA was investigated using isothermal titration calorimetry, UV-vis, fluorescence, circular dichroism (CD) spectroscopy and molecular docking techniques. Steady state fluorescence data revealed that BSA-CS complex formation occurred through static mode of quenching. Negative values of Gibbs free energy change and enthalpy change showed that BSA-CS complexation was spontaneously favorable and enthalpy driven. CS preferentially interacted at Sudlow's site I (sub-domain IIA) of BSA and the finding was further substantiated by molecular docking study. The binding of CS induced changes in secondary motif of BSA resulting decrease of α-helical content as evident from CD. We explored detailed thermodynamic and structural parameters of interaction of CS to BSA that will be helpful for understanding the more precise binding mechanism of the drug at molecular level. Communicated by Ramaswamy H. Sarma